Zn–Catharanthus roseus and Cu–Catharanthus roseus Complexes as Green Organometallic Photosensitizers for DSSC Applications - Yani' Qoriati; Akhmad Al-Bari; Nawafila Februyani; Nely Alfiana Faricha Alfiana Faricha; Ahmad Abil Kamal (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2025)
The global energy crisis and climate change issues have driven the development of environmentally friendly renewable energy sources, one of which is the dye-sensitized solar cell (DSSC) utilizing natural pigment-based photosensitizers. Catharanthus roseus (tapak dara) was selected due to its abundance of secondary metabolites and its potential to be modified into Zn and Cu nanoparticles to enhance stability and efficiency. In this study, tapak dara leaf extract was obtained using ethanol through ultrasonic extraction, then synthesized into Zn and Cu nanoparticles with Zn:Cu ratios of 0:4, 1:3, 2:2, 3:1, and 4:0 via green synthesis. The resulting nanoparticles were deposited onto TiO₂ electrodes, with Pt used as the counter electrode in the DSSC. The cells were tested under 9 mW halogen light. The results revealed that the Zn:Cu ratio influenced crystallite size, morphology, and solar cell efficiency. XRD characterization confirmed the formation of ZnO and Cu phases with crystallite sizes ranging from 9 to 40 nm, while SEM analysis showed nanometer-sized particles with a tendency to agglomerate. The highest efficiency was achieved at a 3:1 ratio, reaching 120 × 10⁻⁴ %, indicating that Zn/Cu–tapak dara nanoparticles hold strong potential as effective photosensitizers.